Remarks at Media Roundtable during Annual Meetings 2021 - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass discussed a broad range of development issues, including the economic outlook, growth, vaccines, debt, climate, and trade. World Bank financing operations will be addressed at the annual meeting as well as our climate change action plan, which aims to help reduce greenhouse gas (GHG) emissions and improve adaptation. We expect global growth of 5.7 percent in 2021 and 4.4 percent in 2022, these are very similar to our projections in the June Global Economic Prospects report. Incoming high-frequency data point to slowing momentum in global activity amid persistent supply chain bottlenecks and COVID-19 surges. Moreover, the global recovery remains dramatically uneven. The outlook is challenging for much of the developing world with lagging vaccination rates, rising inflation, limited policy support, too few jobs, and shortages that extend to food, water, and electricity. As of mid-2021, over half of IDA countries, those are the world’s poorest countries, are in external debt distress or at high risk of it. A comprehensive approach, including debt reduction, swifter restructuring and more transparency is needed to help countries assess and manage their external debt risks and work toward sustainable debt levels and terms. These are fundamental to supporting health systems, education, and infrastructure and creating growth, investment, and prosperity. Enhanced and accelerated implementation of the Common Framework will be critical in achieving this much-needed debt transparency and sustainability.